Hemodynamic response varies across tactile stimuli with different temporal structures. Issue 3 (10th November 2020) - Wang, Luyao; Li, Chunlin; Chen, Duanduan; Lv, Xiaoyu; Go, Ritsu; Wu, Jinglong; Yan, Tianyi
Abstract: Tactile stimuli can be distinguished based on their temporal features (e.g., duration, local frequency, and number of pulses), which are fundamental for vibrotactile frequency perception. Characterizing how the hemodynamic response changes in shape across experimental conditions is important for designing and interpreting fMRI studies on tactile information processing. In this study, we focused on periodic tactile stimuli with different temporal structures and explored the hemodynamic response function (HRF) induced by these stimuli. We found that HRFs were stimulus‐dependent in tactile‐related brain areas. Continuous stimuli induced a greater area of activation and a stronger and narrower hemodynamic response than intermittent stimuli with the same duration. The magnitude of the HRF increased with increasing stimulus duration. By normalizing the characteristics into topographic matrix, nonlinearity was obvious. These results suggested that stimulation patterns and duration within a cycle may be key characters for distinguishing different stimuli. We conclude that different temporal structures of tactile stimuli induced different HRFs, which are essential for vibrotactile perception and should be considered in fMRI experimental designs and analyses. Abstract : We found that HRFs were stimulus‐dependent in tactile‐related brain areas. Stimulation patterns and duration within a cycle may be key characters for distinguishing different stimuli.